Artistic narratives of death: funerary vessels in Attica’s cultural landscape - Christakopoulou, Olga Gioulika; Giamalidi, Mary (Journal of Greek Archaeology, 2025)
The excavation of an ancient cemetery in Voula, Attica, dating to the Late Geometric period, unveiled a remarkable funerary assemblage – a kantharos and amphora pair adorned with symbolic imagery of horses and birds. These vessels, while reflecting the intricate craftsmanship and artistic tendencies of the era, also embody the ideological and symbolic frameworks of the community they served. Central to this study is the dual function of these artifacts, bridging rituals of life and death and highlighting the deceased’s role within both earthly and celestial spheres.